We are given the function:
g(x) = 6 (4)^x
Part A.
To get the average rate of change, we use the formula:
average rate of change = [g(x2) – g(x1)] / (x2 – x1)
Section A:
average rate of change = [6 (4)^1 – 6 (4)^0] / (1 – 0) =
18
Section B:
average rate of change = [6 (4)^3 – 6 (4)^2] / (3 – 2) =
288
Part B.
288 / 18 = 16
Therefore the average rate of change of Section B is 16 times
greater than in Section A.
<span>The average rate of change is greater between x = 2 to x = 3 than between
x = 1 and x = 0 because an exponential function's rate of change increases
with increasing x (not constant).</span>
Answer:
(a, a)
Step-by-step explanation:
actually there are two cases, don't have intersection and have. if have intersection, then they intersect at line y = x or point (a, a) by definition of inverse function.
Answer:
$20?
Step-by-step explanation:
Answer:
y=3
Step-by-step explanation:
(i used point-slope form which is (y1-y2)=m(x1-x2))
(10-y)=7(4-3)
10-y=7
-y=-3
y=3